Agronomic performance of blackberry cultivars in environmental protection area - da Silva Soler, Lorena; Biasi, Luiz Antonio (Comunicata Scientiae, 2020)
The demand for blackberry has been increasing due to the results of studies on its nutraceutical properties. Moreover, the rusticity of its plants allows its cultivation with reduced use of pesticides, becoming feasible to grow it in areas of environmental protection (APA). As a non-traditional crop in the country and its requirement in specific climatic conditions, there is a lack of studies about management techniques and the adaptability of cultivars in different regions. Thus, it is necessary to study phenological behavior and fruit quality in potential regions. Therefore, this work aimed to verify the adaptability of blackberry cultivars in environmental protection area in Pinhais – PR (Brazil), with no use of pesticides, as well as to evaluate the quality of the fruits produced under this condition, focusing on the recommendation of the cultivars more adapted and the best destination of fruits produced. For this, the phenological and productive performance of seven blackberry cultivars: Tupy, Guarani, Cherokee, Xavante, Brazos, Choctaw, and Arapaho were observed during the cycles of 2017/2018 and 2018/2019. Brazos cultivar had the earliest harvest period, Guarani and Xavante cultivars were intermediate and Tupy and Cherokee cultivars were later in the region. The highest yields were obtained with the cultivars Tupy, Guarani, Xavante, Cherokee, and Brazos. The harvest period extended from November to January. Tupy cultivar produces larger fruits and is the most recommended for marketing as fresh fruit. Other cultivars are recommended for industrialization.